Principle and Kinematics Analysis of a New Planetary Roller and Roller Pinion Compound Transmission Device - Lulu Li; Haiwei Wang; Geng Liu; Xiaojun Fu; Shuangshaung Si (Jixie chuandong)
Proposes a new type of transmission device， the planetary roller and roller pinion transmission device， that combines planetary roller screw with trochoid roller rack. The device not only has advantages of planetary roller screw which are compact structure and large bearing capacity， but also has those of trochoid roller rack which are high precision and low noise. The transmission principle of the device is represented and the parameter matching design method of the transmission device is established. The parameter design and three-dimensional modeling of the transmission device are carried out according to the requirements of specific working conditions. The kinematic simulation of the planetary roller and roller pinion composite transmission device is completed by using Adams software. The result validates the basic transmission principle and design feasibility of the transmission device. The influence law of some basic design parameters on the motion characteristics are analyzed and summarized.